Computing the heat flux required for warming up of frozen wooden prisms for veneer production in the beginning of their autoclave steaming. Issue 1 (November 2021) - Deliiski, Nencho; Angelski, Dimitar
Abstract: An approach for computing the heat flux required for warming up of frozen wooden prisms in the regimes for their autoclave steaming at limited heat power of the steam generator, depending on the dimensions of the prisms cross section, wood moisture content, and loading level of the autoclave has been suggested. The approach is based on the use of two personal mathematical models: 2D non-linear model of the temperature distribution in subjected to steaming frozen wooden prisms and model of the non-stationary heat balance of autoclaves for steaming wood materials. For numerical solving of the models and practical application of the suggested approach, a software program was prepared in the calculation environment of Visual FORTRAN Professional developed by Microsoft. Using this program computation and research of the non-stationary change of the processing medium temperature and heat fluxes in an autoclave with a diameter of 2.4 m, length of 9.0 m and loading level of 50% at a limited heat power of the steam generator, equal to 500 kW during the initial part of the steaming in it of frozen beech prisms with different moisture content have been carried out. The suggested approach can be used for computing and model based automatic realization of energy efficient optimized regimes for autoclave steaming of different wood materials.